Determinants and allocative efficiency of milkfish (Chanos chanos) production in polyculture systems in Pangkep District, Indonesia - ASRUDDIN ASRUDDIN; RAHMAWATY A. NADJA; MUSLIM SALAM; ANDI ADRI ARIEF (Asian Journal of Agriculture, 2026)
Abstract. Asruddin, Nadja RA, Salam M, Arief AA. 2026. Determinants and allocative efficiency of milkfish (Chanos chanos) production in polyculture systems in Pangkep District, Indonesia. Asian J Agric 10 (1): g100159. https://doi.org/10.13057/asianjagric/g100159. The use of polyculture systems in milkfish (Chanos chanos) farming is implemented to increase productivity and improve farmers’ income. This study aims to analyze the technical factors affecting milkfish production and to determine the allocative efficiency of the combination of production inputs used by farmers. The research was conducted in Pangkep District, South Sulawesi Province, Indonesia, during the 2023 production cycle. Primary data were collected through structured interviews using questionnaires with 117 milkfish farmers applying polyculture farming systems. A Cobb-Douglas production function was employed to examine the factors influencing milkfish production per production cycle, while an allocative efficiency analysis evaluated the ratio of marginal value product to input price (MVP/Px). The variables observed included land area, seed stocking, additional feed, fertilizer, medicines, labor, and capital. The results show that land area, seed stocking, additional feed, fertilizer, and labor have a positive and statistically significant effect on milkfish production (p < 0.05), whereas medicines and capital do not show a significant effect. The allocative efficiency analysis indicates that several production inputs have not yet been utilized at economically optimal levels. The estimated optimal input levels per farm per production cycle include a land area of 2.117 ha, seed stocking of 15,874 fish, additional feed of 978.528 kg, fertilizer of 318.991 kg, and labor of 45.447 man-days. These findings suggest that improving the allocation of key production inputs could enhance production performance and economic efficiency in milkfish polyculture farming systems